Ergonomic Criteria and Usability Testing of Cut-Resistant Protective Gloves: An Experimental Study - Heydarnia, Sahar; Jalali, Mahdi; Sabzehali, Saied; Zarrin, Majid; Habibi , Ehsanollah (La Medicina del Lavoro, 2025)
Background: Although hand and arm injuries can be prevented with protective gloves, their use may reduce hand dexterity and muscle strength. This study examined the ergonomic criteria and usability of four cut-resistant protective gloves (CRPGs) types to identify the optimal glove choice. Methods: In this experimental study, 22 male participants were tested under five conditions: barehanded, wearing nitrile-coated gloves, gel-coated gloves, material-coated gloves, and foam nitrile-coated gloves. Dexterity was assessed using the Bennett and O’Connor tests; grip and pinch force were measured with a dynamometer, and a goniometer assessed the range of motion. The gloves’ usability was evaluated through the System Usability Scale (SUS) questionnaire. At the same time, localized discomfort in different areas of the hand was assessed using the Local Perceived Discomfort (LPD) questionnaire. Finally, glove comparisons were made using appropriate statistical tests analyzed with SPSS version 24 software. Results: All examined CRPGs significantly lowered finger dexterity scores (p < 0.001). However, the effects of different gloves on hand dexterity varied. Wearing all four gloves reduced grip force, but statistically significant differences in grip force were noted only between the barehanded condition and Glove B (p = 0.004). Using all four gloves increased pinch force, though this increase was statistically significant only between the barehanded condition and Glove D (p = 0.005). Wearing all gloves caused a statistically significant reduction in wrist, palm, and finger range of motion compared to the barehanded condition (p < 0.005). Lastly, there was a significant statistical difference between the gloves regarding usability (p = 0.001) and LPD (p = 0.001). Conclusions: CRPGs can greatly influence hand skills. Glove D, featuring a foam nitrile coating, exhibited the highest finger dexterity compared to the other gloves studied. Considering aspects like sweat resistance and anatomical design, this foam nitrile-coated glove is appropriate for cutting-resistant tasks within various industries.